2009
DOI: 10.1007/s00464-009-0528-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of clinical results between hand-assisted laparoscopic and open splenectomies

Abstract: For splenomegaly, HALS significantly facilitates the surgical procedure and reduces the hospital stay while maintaining the advantages of OS such as tactile sense as well as easy and atraumatic manipulation of enlarged spleens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 25 publications
(26 reference statements)
1
32
0
Order By: Relevance
“…Ιf LS is chosen, it can be performed using the same surgical technique, providing that the ports are placed more caudally on the abdominal wall, directly related to the lower pole of the spleen (30). For these patients, hand-assisted LS has been proposed (11,20,31,32) as an effective, safe and feasible alternative. Analyzing the feasibility of LS in cases of massive splenomegaly (spleen weight >2000 g) in patients with benign hematological disorder, Al-Mulhim (7) concluded that although LS was feasible in 90% of patients, the condition was significantly associated with prolonged operative time, more blood loss, increased postoperative morbidity, longer time to liquid diet and prolonged postoperative hospital stay.…”
Section: Resultsmentioning
confidence: 99%
“…Ιf LS is chosen, it can be performed using the same surgical technique, providing that the ports are placed more caudally on the abdominal wall, directly related to the lower pole of the spleen (30). For these patients, hand-assisted LS has been proposed (11,20,31,32) as an effective, safe and feasible alternative. Analyzing the feasibility of LS in cases of massive splenomegaly (spleen weight >2000 g) in patients with benign hematological disorder, Al-Mulhim (7) concluded that although LS was feasible in 90% of patients, the condition was significantly associated with prolonged operative time, more blood loss, increased postoperative morbidity, longer time to liquid diet and prolonged postoperative hospital stay.…”
Section: Resultsmentioning
confidence: 99%
“…In 1 RCT comparing HALS to OS, median splenic weight for the HALS group was 1200 g, with no conversions. 26 Moreover, spleens weighing consider ably more than 3000 g have been safely removed using HALS. 7,17,19,20,26 …”
Section: 22mentioning
confidence: 99%
“…Once the spleen is within the bag, it is morcelated as necessary and pulled out through the port site. 7,11,25,26,30 Hand-assisted laparoscopic splenectomy has been shown to facilitate the surgical management of massive splenomegaly, allowing a traumatic manipulation of enlarged spleens. In 1 RCT comparing HALS to OS, median splenic weight for the HALS group was 1200 g, with no conversions.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation
“…A better comprehension of the pathophysiology of this disease, has allowed the introduction of modern techniques for its treatment, including the recent minimally invasive techniques using tension-free tape. With the advent of laparoscopic surgery, which has been successfully performed with great advantages compared to the traditional techniques (5)(6)(7)(8), incontinence surgical repair has been also performed with this mini-invasive approach.…”
Section: Introductionmentioning
confidence: 99%